Education for Democratic Intercultural Citizenship - Veugelers, Wiel (Moral Development and Citizenship Education, 2019)
Education for Democratic Intercultural Citizenship (EDIC) is very relevant in contemporary societies. Seven European universities are working together in developing a curriculum to prepare their students for this important academic, societal and political task. The book present their theories and practices. Readership: Scholars in the field of educational studies, in particular moral education and citizenship education and educational change. Researchers, teacher educators, curriculum developers, policy-makers.